Optimalisasi Lahan Terbuka Hijau Melalui Penanaman Tanaman Hijau Dan Bunga Hias - Bunyamin Bunyamin; Siti Munfaqiroh; Yuyuk Liana; Hanif Mauludin; Evi Maria; Dyah Aruning Puspita; Aminul Amin; Edi Sudiarto; Rina Irawati; Irawan Budi Prasetyo; Agussalim Andriansyah (STIE Malangkucecwara, 2022)
Community service activities are a collaboration between STIE Malangkuҁeҁwara Malang and the Sabililah Polyclinic, Malang City. The form of this activity is the use of open land around the Sabililah Polyclinic, Malang City by planting various green plants and various kinds of flowers. The results of the activities of planting green plants and ornamental flowers and pots can provide a beautiful, cool, and beautiful environment for the Sabilillah Polyclinic so that visitors and employees feel more comfortable